Can Selective Immigration Policies Reduce Migrants' Quality? - Simone Bertoli; Vianney Dequiedt; Yves Zenou (Institute for the Study of Labor (IZA), 2015)
Destination countries can adopt selective immigration policies to improve migrants' quality. Screening potential migrants on the basis of observable characteristics also influences their self-selection on unobservables. We propose a model that analyzes the effects of selective immigration policies on migrants' quality, measured by their wages at destination. We show that the prevailing pattern of selection on unobservables influences the effect of an increase in selectivity, which can reduce migrants' quality when migrants are positively self-selected on unobservables. We also demonstrate that, in this case, the quality-maximizing share of educated migrants declines with the scale of migration.
Keywords: F22; K37; J61; 330; migrants' quality; self-selection; selective policies